2012
DOI: 10.1016/j.eurpsy.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of the “Continuation of Care” model in “revolving-door” patients

Abstract: COC via inpatient follow-up significantly reduces the number and length of hospitalizations in "revolving door" psychiatric patients as compared to the traditional system of follow-up in an outpatient clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…Follow-up in the ward, by the same staff, significantly reduced the number and length of hospitalizations as compared to the traditional system of follow-up in an outpatient clinic [80]. In one study continuity of treatment made no difference for affective disorders patients but it protected schizophrenic patients from rehospitalisation [59] while in another intervention study even if a reduction in total readmissions could not be proved to be significant, a decrease of involuntary readmissions was observed [81].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up in the ward, by the same staff, significantly reduced the number and length of hospitalizations as compared to the traditional system of follow-up in an outpatient clinic [80]. In one study continuity of treatment made no difference for affective disorders patients but it protected schizophrenic patients from rehospitalisation [59] while in another intervention study even if a reduction in total readmissions could not be proved to be significant, a decrease of involuntary readmissions was observed [81].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous interventions instead encompassed a 'boundary spanning' element or agent, (i.e. a ward nurse in the community or a community nurse attending ward meetings) (18)(19)(20), which often had implications in terms of reducing readmissions (8,21). When studying stroke populations, researchers found that no single transition intervention can facilitate knowledge transfer and that a combined approach is often needed focused on three main elements: 1) information systems/technologies (an effective system that allows for the transfer of explicit knowledge), 2) roles (dedicated professional roles to support discharge planning), and 3) group activities (interprofessional or interorganizational group activities) (22).…”
Section: Introductionmentioning
confidence: 99%
“…There were some interventions included in the review that did not fit within the aforementioned primary categories, these groups had 3 or fewer studies, see table 2. These were categorised as pharmacy interventions [11,12] (medications focused interventions led by pharmacists), needsorientated discharge planning [44,49] (discharge planning interventions led by the needs of individuals), intervention to prevent homelessness (an intervention developed by Forchuk et al [10,50] focused only on homeless individuals), transitional care model (a nurse-based in home initiative) [51,52], whole care pathway initiatives [53,54] (that consider multiple agencies in the care pathway) and multi-component models [55][56][57] (using multiple interventions simultaneously). Despite studies reporting on these interventions they tended to be single instances and do not provide sufficient evidence for narrative synthesis on a categorical level.…”
Section: Other Interventionsmentioning
confidence: 99%
“…The most common challenge that the interventions aimed to solve was readmission to an acute ward within a given short-term period, sometimes indicative of shortcomings in service provision [6,18,53,54,[58][59][60][61][62]25,26,28,33,36,38,40,41]. Whilst some studies found evidence for a reduction in readmission due to the interventions [26,28,40], many failed to evidence this effect [6,33,36].…”
Section: Reducing Readmissionmentioning
confidence: 99%
See 1 more Smart Citation